2011
DOI: 10.15283/ijsc.2011.4.1.18
|View full text |Cite
|
Sign up to set email alerts
|

TGF-beta Family Signaling in Embryonic Stem Cells

Abstract: TGF-beta Family Signaling in Embryonic Stem Cells Kyung-Soon Park Department of Biomedical Science, College of Life Science, CHA University, Seongnam, KoreaLigands of transforming growth factor beta (TGF-β) family members have been implicated in the development and patho-physiological process of various organs. Embryonic stem cells (ESCs) are characterized by their ability to proliferate indefinitely and differentiated into all three germ layer cells, which are termed as pluripotency and self-renewal, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
2
19
0
1
Order By: Relevance
“…Confirming that, up-regulation of the TGF␤ pathway was observed in REST-deficient NT embryos, revealing TGF␤ pathway is suppressed by REST in NT embryos. TGF␤ pathway has been implicated in the development and maintenance of various organs (19,20), and is necessary for the maintenance of self-renewal and pluripotency of both human and mouse ESCs (21). During embryonic development, the pathway is believed to play critical roles in the specification of cell identities in embryonic and extra embryonic lineages of the post-implantation embryo (19,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Confirming that, up-regulation of the TGF␤ pathway was observed in REST-deficient NT embryos, revealing TGF␤ pathway is suppressed by REST in NT embryos. TGF␤ pathway has been implicated in the development and maintenance of various organs (19,20), and is necessary for the maintenance of self-renewal and pluripotency of both human and mouse ESCs (21). During embryonic development, the pathway is believed to play critical roles in the specification of cell identities in embryonic and extra embryonic lineages of the post-implantation embryo (19,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Lefty is a member of the transforming growth factor-β (TGF-β) superfamily with two variants that are respectively designated as human Lefty1 (Lefty B in mouse) and human Lefty2 (Lefty A in mouse). 2 Lefty is a secretory protein, and the relative molecular weight of preproprotein is 42 kDa. After cleavage with proteolytic enzymes at two sites (Arg77 and Arg135), two mature peptides, 34 and 28 kDa, are respectively formed.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, this function duality is attributed to the fact that Smads activate different sets of target genes in pluripotent and differentiating cells, depending on its level of activation and the availability of co-factors [83]. Indeed, TGF-ß superfamily ligands, including TGF-ß isoforms, Activin, Nodal, growth and differentiation factors (GDFs), anti-Müllerian hormone (AMH), and BMPs, bind to and activate type I (1-7) and II (1-5) receptor serine/threonine kinases, which in turn, together with activin-receptor like kinases (Alk) (1-7), phosphorylate the regulatory Smad proteins (R-Smad 1, 2, 3, 5, 8) [195].…”
Section: Specific Protein Kinases and Associated Signaling Pathwaymentioning
confidence: 99%
“…The recent comparative receptor tyrosine kinase expression and phosphorylation profiling for hESCs and hiESCs performed by Son et al [80] revealed up-regulation of EPHA1, ERBB-2/EGFR-2, FGFR-4 and VEGFR-2 and down-regulation of AXL, EPHA4, PDGFRß and TYRO3 as related to the maintenance of hESCs. As of yet, the basic PKs signaling framework described in PSCs is defined by Insulin/IGF/FGF/LIF signaling through PI3K [81, 82], TGF-ß/Activin A/Nodal signaling through Smad [83, 84], FGF signaling through the Ras/MAPK/Raf/Mek/Erk pathway [82, 85], and the canonical Wnt/Gsk3 signaling pathway [86, 87]. The JAK/STAT [88] and Src pathways [89] have also a significant impact on this process.…”
Section: General Introduction To Protein Kinases and Pluripotencymentioning
confidence: 99%